2017
DOI: 10.1007/s00590-017-1905-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and situations of anterior cruciate ligament injuries in professional male soccer players: a YouTube-based video analysis

Abstract: Level IV, case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 34 publications
0
70
1
1
Order By: Relevance
“…29 Also, the greatest number of injuries occurred in defenders (43%), which could reflect both the generally higher absolute numbers of defenders on normal rosters (which usually utilize modules with 4 defenders) and also indirectly pointing out pressing as one of the most common injury mechanisms. 3,8,15,37…”
Section: Discussionmentioning
confidence: 99%
“…29 Also, the greatest number of injuries occurred in defenders (43%), which could reflect both the generally higher absolute numbers of defenders on normal rosters (which usually utilize modules with 4 defenders) and also indirectly pointing out pressing as one of the most common injury mechanisms. 3,8,15,37…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, during the redirection phase greater hip abduction, greater trunk lean angles at IC and greater hip adductor moments were observed during the 90° cut [ 26 ]. Greater hip abduction has been reported to be a biomechanical risk factor associated with knee abduction moments (KAM—synonymous with knee valgus moments for the purpose of this review) [ 39 ], thus ACL injury risk [ 78 ], and is also a commonly observed visual characteristic of non-contact ACL injuries [ 9 , 79 ]. This abducted lower extremity position is often discouraged in ACL injury prevention programmes [ 44 ], but increased hip abduction is necessary to create a larger ML COM-COP (to create a lateral foot plant) distance [ 26 , 27 ] and subsequent lateral propulsion for executing sharper CODs [ 25 , 38 , 80 ].…”
Section: Effect Of Angle On Cod Biomechanicsmentioning
confidence: 99%
“…Knee injuries are common in male professional soccer players, 1 where the anterior cruciate ligament (ACL) injury has interested many researchers. [2][3][4][5][6][7] There is, however, a paucity of studies which focus primarily on injuries to the other major knee ligaments. Previous studies from the Union of European Football Associations (UEFA) Elite Club Injury Study have reported on ACL injuries [8][9][10][11][12] and on medial collateral ligament (MCL) injuries.…”
Section: Introductionmentioning
confidence: 99%